AB0079 Presence of extracellular rna and rnase in synovial tissue and synovial fluid of patients with rheumatoid arthritis. (23rd January 2014) - Zimmermann, B.; Fischer, S.; Rickert, M.; Rehart, S.; Lehr, A.; Müller-Ladner, U.; Preissner, K.T.; Neumann, E.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by the destruction of cartilage and bone in affected joints. It is known that various pro-inflammatory and pro- destructive factors are increased in the inflamed joint. However, little is known about the role of extracellular RNA (exRNA) in RA. The role of intracellular RNA in the protein biosynthesis is well known in contrast to the effects mediated by exRNA. Pro-coagulative properties and an increased hyper-permeability in the blood-brain-barrier have been described for exRNA. Therefore, the presence and effects of exRNA and exDNA were analyzed in this study. Objectives: To analyze the RNase activity in synovial fluid as well as the presence and the localization of exRNA in the synovial tissue of patients with RA in comparison to other joint diseases. Methods: The RNase activity in synovial fluid (RA: n=4; osteoarthritis (OA): n=3 and psoriatic arthritis (PsA): n=5) was analyzed using the Quant-iT™ RNA Assay Kit. To identify exRNA in the synovium, the tissue of RA and OA patients (n=3 each) were stained with 4′ , 6-diamidin-2-phenylindole (DAPI) to locate DNA and SYTO® RNASelect™ Green Fluorescent Stain to locate RNA. To distinguish between the lining layer and the sublining, serial tissue sections were stained with hematoxylin/eosin. The localization of RNA was determined by comparing the HE-staining with the RNA and DNA-staining of serial sections. Results: In the synovial fluid of patients with RA (20.1±3.61) and PsA (21.3±2.5), a lower RNase activity was detectable in comparison to OA patients (35.8±4.5). A statistical significance was seen when comparing PsA and OA samples (p=0.033), and RNase activity was inversely correlated to the CRP serum level (r=-0.43). In all regions of the synovium, RNA and DNA signals could be detected. After merging both signals, a co-localization within the nuclei of the cells was detectable. Furthermore, in the lining layer of RA and OA patients a strong cytoplasmatic as well as exRNA signal could be observed, especially in the RA lining layer. Conclusions: ExRNA is present in increased amounts in the synovial lining layer of RA patients but can also be detected in the synovium of OA patients. In synovial fluid, RNase activity appears to be reduced in patients with chronic inflammation (RA and PsA) in comparison to OA. As we previously could show pro-inflammatory effect of exRNA on RASF, the elevated amounts of exRNA could represent a new pro-inflammatory parameter that is active in chronic inflamed tissue and may contribute to the maintenance and chronification of inflammation. Disclosure of Interest: None Declared